Urgensi Kalibrasi Arah Kiblat dalam Penyempurnaan Ibadah Salat - Dhiauddin Tanjung (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2018)
In the implementation of one's prayer service is required to face the direction of Qibla as a valid requirement of prayer. Understanding of facing the Qiblah should be understood properly and maximally so that efforts to face the Qiblah can be done well and precisely. This paper explains that the obligation of facing the Ka’bah is for the one who is able to see the Ka’bah directly. But for those who are far from Mecca and cannot see the Ka’bah directly, the majority of the Muslim scholars only oblige facing towards the Kaaba (jihah al-ka’bah). However, in retrospect, the ulama have a strong opinion that for the one who can see the Kaaba, and the one who cannot see the Kaaba, but in fact he can be wise to know the direction to the Kaaba (jihah al-Ka’bah), then they are obliged to face the building of the Kaaba ('ainul Ka’bah). From the term ‘ainul ka’bah and jihah al-ka’bah, it is actually the one point to be taken that is the Kaaba in Mecca. ‘Ainul ka’bah is the building of the Kaaba itself, whereas the jihah of al-ka’bah is the direction towards the Kaaba. Therefore, to lead to the Kaaba, it should not be carelessly facing. Especially with the existing science and technology, the calculation to lead to the point of the Kaaba becomes easier with accuracy that can be accounted for. If so, science and technology can participate to play a role in completing the worship of Muslims, i.e. facing the Qiblah more appropriate for the validity of worship.